ERGONOMIC RISK LEVEL AND MUSCULOSKELETAL COMPLAINTS DISORDERS (MSDS) IN GALLON SHUTTERS IN THE QUALITY AREA OF QUEEN AGUNG BENGKULU CITY - SRI MULYATI; APLINA KARTIKA SARI (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
Ergonomics is a field of study that studies human interaction with elements in the system, so that various theories and methods will be produced to optimize the performance and performance of the overall system. While Musculoskeletal disorders (MSDs) are complaints felt by workers such as muscle pain, and cartilage pain. This study aims to determine the ergonomics and complaints of musculoskeletal disorders (MSDs). Based on an initial survey of 5 drinking water depot workers about whether they feel pain in the body when they work, it turns out there are complaints such as pain in some parts of their body such as back pain 3 people, neck 2 people, and others after they work. This research was a descriptive observational study, the sample in this study was 35 drinking water depot workers using total sampling. From the univariate results of 35 workers had a moderate level of ergonomic risk of 32 (91.4%), while complaints of Musculoskeletal disorders (MSDs) experienced by workers were more dominant while complaints of musculoskeletal disorders were 21 (60%). Workers are expected to pay attention to the ergonomics of work positions carried out when carrying out work activities that have a sufficiently long period of time, thereby reducing complaints of Musculoskeletal disorders experienced by workers.